2007
DOI: 10.1073/pnas.0609444104
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of human T cell leukemia virus type 1 to APOBEC3G restriction is mediated by elements in nucleocapsid

Abstract: Human T cell leukemia virus type 1 (HTLV-1) has evolved a remarkable strategy to thwart the antiviral effects of the cellular cytidine deaminase APOBEC3G (hA3G). HTLV-1 infects T lymphocytes in vivo, where, like HIV-1, it is likely to encounter hA3G. HIV-1 counteracts the innate antiviral activity of hA3G by producing an accessory protein, Vif, which hastens the degradation of hA3G. In contrast, HTLV-1 does not encode a Vif homologue; instead, HTLV-1 has evolved a cis-acting mechanism to prevent hA3G restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 36 publications
2
119
0
Order By: Relevance
“…Some retroviruses, such as HIV, simian immunodeficiency virus (SIV), and feline immunodeficiency virus (FIV), encode Vif proteins that bind APOBEC3 proteins and target them for degradation in virus-producing cells. Additionally, the Bet protein of feline foamy viruses inhibits APOBEC3 by as yet undetermined means (16) and human T-cell leukemia virus I prevents packaging of APOBEC3G, although not APOBEC3A, 3B, or 3H (47,48). However, APOBEC3 inhibits infection by a number of viruses that encode no apparent vif-or bet-like genes, and how these viruses overcome restriction is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Some retroviruses, such as HIV, simian immunodeficiency virus (SIV), and feline immunodeficiency virus (FIV), encode Vif proteins that bind APOBEC3 proteins and target them for degradation in virus-producing cells. Additionally, the Bet protein of feline foamy viruses inhibits APOBEC3 by as yet undetermined means (16) and human T-cell leukemia virus I prevents packaging of APOBEC3G, although not APOBEC3A, 3B, or 3H (47,48). However, APOBEC3 inhibits infection by a number of viruses that encode no apparent vif-or bet-like genes, and how these viruses overcome restriction is not known.…”
Section: Discussionmentioning
confidence: 99%
“…However, restriction factors for HTLV-1 have not been studied extensively. It has been reported that APO-BEC3G suppresses replication of HTLV-1 whereas Gag protein inhibits incorporation of APOBEC3G into the virion (32). Recently, SAMHD1 has been reported to suppress replication of HTLV-1 in monocytes (33).…”
Section: Discussionmentioning
confidence: 99%
“…More straightforward alternatives might be to avert APOBEC proteins by not encapsidating them into virions (e.g. human T-cell leukaemia virus type-I, HTLV-I, and Mason-Pfizer monkey virus, M-PMV ) (Doehle et al 2006;Derse et al 2007) or, perhaps, by simply replicating in nonexpressing cells (Delebecque et al 2006).…”
Section: Anti-hiv-1 Phenotypes Of Diverse Human Apobec Proteinsmentioning
confidence: 99%